A novel electrochemical aptamer–antibody sandwich assay for the detection of tau-381 in human serum. Issue 15 (13th July 2018) - Shui, Bingqing; Tao, Dan; Cheng, Jing; Mei, Yong; Jaffrezic-Renault, Nicole; Guo, Zhenzhong
Abstract : A novel electrochemical biosensor was developed to detect tau-381 in human serum by aptamer–antibody sandwich assay. Abstract : Tau protein plays a crucial role in the pathogenesis of Alzheimer's disease (AD). However, the assay to detect low concentrations of tau protein is a great challenge for the early diagnosis of AD. We will outline a novel aptamer–antibody sandwich assay based on an electrochemical biosensor for the detection of tau-381 in human serum. To improve the detection sensitivity, the aptamer–antibody sandwich assay for the detection of tau-381 was developed by using a tau antibody (anti-tau) and an aptamer specific to tau-381 as the recognition element and cysteamine-stabilized gold nanoparticles (AuNPs) for signal amplification. Differential pulse voltammetry (DPV) was employed to record the signal response of tau-381 with different concentrations. The tau-381 concentration ranged from 0.5 pM to 100 pM. The responses of DPV measurements showed excellent results in this dynamic range. This simple, rapid, highly sensitive and specific assay gave a low limit of detection (LOD) of 0.42 pM for tau-381. The feasibility and reliability of the assay were verified by testing tau-381 in human serum from patients with AD. Thus, this method could prove valuable in diagnosing AD within the early stages of the disease.